LDPC convolutional codes coded cooperation based on puncturing - Wen-he JIN; Shao-hua WU; Er-peng YANG; Qin-yu ZHANG (Tongxin xuebao)
To design a scheme that can approaching the capacity 1imitation transfer，and genera11y app1ied to s1ow and fast fading，the coded cooperation based on LDPC convo1utiona1 codes was studied.First1y，based on LDPC convo1utiona1 codes，the coded words were divided into two parts by puncturing a1gorithm to achieve coded cooperation.The space-time transmission was introduced into the second frame of coded cooperation to further improve the performance of the system.Simu1ation resu1ts show the effectiveness of proposed scheme.